Advanced design as reframing practice: Ethical challenges and anticipation in design issues. (August 2015) - Celaschi, Flaviano; Celi, Manuela
Highlights: ADD reframing identify and experiment new ways of designing the futures. The ethical challenges are integral part of the design since its early beginnings. The client-based crisis brings the design to venture into "problem finding". ADD ethics introduces a dimension that includes the effects over time. ADD is a mediator between design culture and future studies. Abstract: Advanced Design (ADD) is a branch of industrial design that directs and uses the tools, practices and knowledge of conventional industrial design in long-term projects, or in projects that are addressed to a distant future. Recently, ADD has focused its attention on projects that are not governed by a client in order to search for innovation stimuli that come from extreme situations or far from the aim of the project. It also focuses on continuous innovation processes in which the designer is not the only creative actor of the process and often only helps draw the route of innovation, instead of drawing it alone. Although the ethical debate has always been alive in conventional industrial design, considering this renewed horizon of ADD, a particular reflection on the concepts of ethics, time and the designer's responsibility, is necessary. This paper describes the transformation of the traditional designer considered to be the demiurge of fashion and industrial products into a manufacturer of possible futures and co-author of futurist reframing.